การพัฒนารูปแบบผ้าย้อมครามสำหรับคนรุ่นใหม่ - Anurat Saithong อนุรัตน์ สายทอง (Creative Science, 2015)
บทคัดย่อ การวิจัยเรื่องการพัฒนารูปแบบผ้าย้อมครามสำหรับคนรุ่นใหม่ มีจุดประสงค์ 3 ประการ คือ (1) เพื่อศึกษาความต้องการรูปแบบผ้าย้อมครามของคนรุ่นใหม่ (2) เพื่อพัฒนาผ้าและผลิตภัณฑ์ต้นแบบตามความต้องการของคนรุ่นใหม่ (3) เพื่อเผยแพร่ข้อมูลความต้องการรูปแบบผ้าและจัดแสดงผ้าตัวอย่างที่พัฒนาขึ้น กิจกรรมการวิจัยมี 4 กิจกรรม คือ (1) รวบรวมข้อมูลความต้องการรูปแบบผ้าย้อมครามของคนรุ่นใหม่ โดยการสัมภาษณ์ (2) จัดเสวนา ออกแบบผ้า และพัฒนาผ้าตัวอย่าง (3) วิพากษ์ผืนผ้าตัวอย่าง ออกแบบ และสร้างผลิตภัณฑ์ (4) จัดแสดงผลิตภัณฑ์ต่อสาธารณะและเก็บข้อมูลความพึงพอใจในผืนผ้าและผลิตภัณฑ์ ผลการวิจัย พบว่า คนรุ่นใหม่ อายุระหว่าง 20-50 ปี ส่วนใหญ่ต้องการผ้าย้อมครามที่ใช้เส้นใยฝ้าย ย้อมครามล้วน สีเข้ม เนื้อบางสม่ำเสมอ มีลายเล็ก ๆ กระจายบนผืนผ้า นำความต้องการผ้าย้อมครามข้างต้นเสนอให้ผู้ร่วมเสวนาที่เกี่ยวข้องกับผ้าย้อมครามทั้งผู้ผลิต ผู้ค้า ผู้ใช้ ผู้ส่งเสริม และนักวิจัย ระดมความคิด เพื่อออกแบบผืนผ้า แล้วทอเป็นผืน ได้ผ้าทั้งหมด 7 ลาย 7 ผืน นักวิจัยร่วมกับผู้บริโภค ผู้ค้า และช่างตัดเย็บ วิพากษ์ผืนผ้า ออกแบบ และตัดเย็บเป็นผลิตภัณฑ์ได้ 10 ชิ้น นำผลิตภัณฑ์เสนอต่อสาธารณะด้วยการเดินแบบ 2 ครั้งในงานเทศกาลของจังหวัดสกลนคร และจัดนิทรรศการแสดงผลิตภัณฑ์พร้อมสัมภาษณ์ความพึงพอใจต่อผืนผ้าและผลิตภัณฑ์ พบว่า ผลิตภัณฑ์ที่ได้รับความพึงพอใจมากที่สุดตามลำดับมีดังนี้ เสื้อลำลองจากผ้าลายผาแดง - ไอ่คำ ชุดสตรีลายกระบองเพชร และชุดสตรีลายหมี่ประยุกต์ คำสำคัญ : รูปแบบผ้า, ผ้าย้อมคราม, คนรุ่นใหม่ Abstract The study on the development of indigo-dyed cloths’ pattern for new generations had 3 objectives, which were 1) to study the new generations’ demand on indigo-dyed textile; 2) to improve the fabric and the model products according to the new generations’ demands; 3) to distribute information on textile demands and exhibit the developed textile samples. There were 4 research activities, which were 1) information gathering of the new generations’ demands on indigo-dyed cloths’ pattern by interviewing; 2) holding a seminar, designing the textile and developing the textile model; 3) examining the textile model, designing and manufacturing the product; 4) exhibiting the product model to the public and collecting the data on the satisfaction on the model and product. The research result yielded that most of the new generations aged between 20-50 years old preferred indigo-dyed textile made from cotton with pure indigo dyeing in dark color, smoothly thin cloth with small patterns over the textile. The said result was presented to the seminar participants who were manufacturers, traders, consumers, promoters and researchers, to brainstorm together to design and create the textile, totally 7 textile in 7 different patterns. The researchers with the consumers, traders and tailors together examined the fabric, designed and tailored the textile into 10 products. The products were then being presented to the public in 2 fashion shows in Sakon Nakhon’s provincial fair. An exhibition was also held and satisfaction of participants was being asked. It was found that the products that gained the most satisfaction were Phadeang-Aikham shirt, cactus-pattern woman suit and applied Mhee-pattern woman suit respectively. Keywords: Cloths’ Pattern, Indigo-dyed Textile, The New Generations